The rarity of gonococcal arthritis in association with HIV infection - Maharaj, Rasha; Mody, Girish M (The Journal of Infection in Developing Countries, 2014)
Gonococcal urethritis is common with HIV, but gonococcal arthritis is rare. We report two HIV-positive patients with gonococcal arthritis and review previously published reports. A 27-year-old HIV-positive female presented with a pustular skin rash and acute oligoarthritis. Neisseria gonorrhoeae was cultured from the right elbow aspirate. The second patient, a 24-year-old HIV-positive female on zidovudine for one month, presented at 28 weeks gestation with acute oligoarthritis and peroneal tenosynovitis. Neisseria gonorrhoeae was cultured from the throat swab. Both patients responded to ceftriaxone. Gonococcal arthritis must be considered in HIV patients with acute arthritis.